POTENSI PENGEMBANGAN ASURANSI SYARIAH USAHA TANI PADI DI ACEH BESAR (PENDEKATAN ANALISIS SWOT) - Murni, Seri; Fithriady; Ulmiana, Fira (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2023)
Rice Farming Business Insurance (AUTP) is social insurance implemented by the government to provide benefits to its people, where this insurance can help rice farmers who experience losses due to attacks by plant organisms, outbreaks of infectious diseases, and other disturbances that cause crop failure for farmers. In general, the concept of Sharia AUTP can be carried out following the existing AUTP, but it needs to be adjusted to the basic principles of Sharia insurance. This study aims to identify and analyze the Strengths and Opportunities as well as the Weaknesses and Threats of the development of Rice Farming Business Insurance in Aceh Besar. The method used is descriptive qualitative analysis, with data collection techniques through interviews and documentation. The results of the study show that the development of sharia insurance for rice farming is in quadrant III which illustrates that sharia insurance for rice farming has a huge opportunity to develop in Aceh Besar, but on the other hand, it also experiences some internal weaknesses. The strategy that can be utilized in the development of sharia insurance for rice farming is the WO strategy, namely 1) Increasing the socialization of sharia insurance for rice farming to the public to increase farmers' interest in insurance, 2) The government needs to make special regulations governing sharia insurance for rice farming. Keywords: Sharia Insurance, Rice Farming Business Insurance, SWOT Analysis